Integrating data sources - Matiaško, Karol; Babišová, Martina; Vajsová, Monika (Univerzita Pardubice, 2006)
Integrating heterogeneous data sources is a big deal for most companies, organizations, universities ... Thanks to this every organization can yield the most important and relevant information for every user (in sense of employee, manager, student, professor,...) without bigger effort. Our paper describes what everything can be integrated in portal and how easily it can be done. The biggest problem for us is to choose the most effective and functional technique for solving our problems.
Integrácia dátových zdrojov
Keywords: datové zdroje; Integrace; rozsáhlé informační systémy; portálová řešení